1988
DOI: 10.1136/jmg.25.3.164
|View full text |Cite
|
Sign up to set email alerts
|

Intellectual development in Apert's syndrome: a long term follow up of 29 patients.

Abstract: SUMMARY Twenty-nine patients with Apert's syndrome were ascertained through hospital records.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
38
0
12

Year Published

1990
1990
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(50 citation statements)
references
References 3 publications
0
38
0
12
Order By: Relevance
“…One possible explanation for these discrepant findings is the higher percentage of children who have Apert syndrome (23%) included in the study of Da Costa compared with our study (8%), because Apert syndrome has been found to be associated with lower FSIQs. 8,20 Flapper and colleagues reported FSIQs of more than 1 SD below the normative mean in 32% of their patients who have Crouzon/Pfeiffer (n = 16). However, that study used a highly selected sample of patients referred to the hospital.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One possible explanation for these discrepant findings is the higher percentage of children who have Apert syndrome (23%) included in the study of Da Costa compared with our study (8%), because Apert syndrome has been found to be associated with lower FSIQs. 8,20 Flapper and colleagues reported FSIQs of more than 1 SD below the normative mean in 32% of their patients who have Crouzon/Pfeiffer (n = 16). However, that study used a highly selected sample of patients referred to the hospital.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] Table 2 provides details on these studies. Overall, these pioneering studies reported divergent outcomes on intellectual functioning of children who have well-known syndromes.…”
mentioning
confidence: 99%
“…In previous studies, Patton et al 10 , Léfèvre et al 11 , it was observed among 70 patients, with no sex prevalence, being 50% of men and 50% of women, respectively. After these studies it can be concluded that most of the patients with Apert's syndrome is mental faulty in different levels.…”
Section: Discussionmentioning
confidence: 99%
“…Its morbidity is significant, since approximately half of affected individuals have some degree of mental retardation with IQs ranging from less than 35 to the normal range (Renier et al, 1996;Patton et al, 1988;Sarimski, 1997). Prenatal diagnosis of Apert syndrome in sporadic cases is challenging because the characteristic sonographic features of craniosynostosis may not present until the third-trimester (Filkins et al, 1997).…”
Section: Discussionmentioning
confidence: 99%